The enhancement of the N1 wave elicited by sensory stimuli presented at very short inter-stimulus intervals is a general feature across sensory systems. - An Li Wang (Public Library of Science (PLoS), 2008)
Background A paradoxical enhancement of the magnitude of the N1 wave of the auditory event-related potential (ERP) has been described when auditory stimuli are presented at very short (< 400 ms) inter-stimulus intervals (ISI). Here, we examined whether this enhancement is specific for the auditory system, or whether it also affects ERPs elicited by stimuli belonging to other sensory modalities. Methodology and principal findings We recorded ERPs elicited by auditory and somatosensory stimuli in 13 healthy subjects. For each sensory modality, 4800 stimuli were presented. Auditory stimuli consisted in brief tones presented binaurally, and somatosensory stimuli consisted in constant-current electrical pulses applied to the right median nerve. Stimuli were delivered continuously, and the ISI was varied randomly between 100 and 1000 ms. We found that the ISI had a similar effect on both auditory and somatosensory ERPs. In both sensory modalities, ISI had an opposite effect on the magnitude of the N1 and P2 waves: the magnitude of the auditory and the somatosensory N1 was significantly increased at ISI < or = 200 ms, while the magnitude of the auditory and the somatosensory P2 was significantly decreased at ISI < or = 200 ms. Conclusion and significance The observation that both the auditory and the somatosensory N1 are enhanced at short ISIs indicates that this phenomenon reflects a physiological property that is common across sensory systems, rather than, as previously suggested, unique for the auditory system. Two of the hypotheses most frequently put forward to explain this observation, namely (i) the decreased contribution of inhibitory postsynaptic potentials to the recorded scalp ERPs and (ii) the decreased contribution of 'latent inhibition', are discussed. Because neither of these two hypotheses can satisfactorily account for the concomitant reduction of the auditory and the somatosensory P2, we propose a third, novel hypothesis, consisting in the modulation of a single neural component contributing to both the N1 and the P2 waves.